SDK1-ALK Fusion in a Lung Adenocarcinoma Patient With Excellent Response to ALK Inhibitor Treatment: A Case Report - Ma, Lin; Xiao, Junjuan; Guan, Yaping; Wu, Dongfang; Gu, Tiantian; Wang, Jun (Frontiers in Oncology, 2022)
Background: Rearrangements of Anaplastic lymphoma kinase (ALK) have been discovered as a novel driver mutation in patients with non–small-cell lung cancer (NSCLC). Patients’ responses to ALK tyrosine kinase inhibitors (TKIs) may vary depending on the variations of ALK rearrangements they have. It is imperative for clinicians to identify druggable ALK fusions in routine practice. Case Presentation: In this study, we discovered a rare ALK rearrangement type (SDK1–ALK) in a Chinese lung adenocarcinoma patient who responded well to ALK inhibitor SAF-189s. The positive expression of ALK in lung biopsy tissue was verified by IHC analysis. A new SDK1-ALK fusion was discovered using NGS. The patient was treated with SAF-189s (160 mg per day) as a first-line therapy and went into continuous remission, with a 12 months progression-free survival at the last follow-up. Conclusion: This is the first case of SDK1-ALK fusion with an excellent response to an ALK inhibitor, which will provide better understanding of ALK-TKI applications for NSCLC patients with ALK fusion in the future.